Studies on Fibres of Some Azoaromatic Polyimides - RAJENDIRAN, T.V.; ANBUSELVAN, C. (Asian Journal of Chemistry, 2010)
Three new azoaromatic polyimides were synthesized by condensing 3,3',4,4'-azobenzene tetra carboxylic dianhydride and 4,4'-diaminodiphenyl/ 4,4'-diaminoazobenzene/2,2-bis(4-p-aminophenoxy) phenyl]- propane. These polyimides were drawn into fibres with different experimental conditions. Their physical, mechanical and morphological properties were studied. The structure of polyimides were also confirmed by pyrolysis-GC-mass spectra.